(Im)Balancing Acts: Criminalization and De-Criminalization of Social and Public Health Problems. Issue 4 (2022) - Gilbert, Keon L.; Chang, Robert S.
Abstract: Racially disparate policing, prosecution, and punishment harm individuals, families, and communities. These practices must be understood within the context of the development of the criminal legal system as a means of racialized social control. This context permits a critical examination of the way criminalization has been and is still deployed to subject poor and racialized communities to systemic injustices. This commentary frames a call for interventions to integrate a health justice approach to ensure that they advance racial and health equity to promote the well-being of individuals, families, and communities.